Praktik Intellectual Capital Disclosure Perusahaan yang Terdaftar di Bursa Efek Indonesia - Djoko Suhardjanto; Mari Wardhani (Jurnal Akuntansi dan Auditing Indonesia, 2010)
The objective of this research is to examine the level of intellectual capital disclosure in annual report prepared by listed firms on IDX. This research examines the relationship between intellectual capital disclosure as a dependent variable and firm’s characteristic (size, profitabil¬ity, leverage, and length of listing on IDX and corporate governance provisions) as independent variables.This research used 80 annual reports 2007 of Indonesian listed firms. Sample was selected using proportional purposive sampling method. The result shows that the average level of intellectual capital disclosure is only 35%. Multiple regression analysis is used to test the hypothesis. Statistical analysis demonstrates that Firm’s Size and Profitability are predictors to the level of intellectual capital disclosure. The implication is that firm’s with high total asset and profitability should be more concern to report intellectual capital information because it’s the one of crucial information that considered by investor, to reduce “information gap” and to increase shareholder value. Keywords: intellectual capital disclosure, firm’s characteristics